ASTI benchmarking tool for agricultural R&D in West Asia and North Africa - Agricultural Science and Technology Indicators (International Food Policy Research Institute, 2015)
The ASTI benchmarking tool enables cross-country comparisons and rankings of key agricultural R&D spending and capacity indicators.